Becoming a mother during the COVID‐19 national lockdown in Italy: Issues linked to the wellbeing of pregnant women. (1st September 2021) - Smorti, Martina; Ponti, Lucia; Ionio, Chiara; Gallese, Marta; Andreol, Angelica; Bonassi, Lucia
Abstract : The COVID‐19 pandemic and consequent lockdown represent risk factors for the mental health of pregnant women. We explored the impact of COVID‐19 restriction policies on psychological health, analysing the predictive role of social support on maternal wellbeing. A total of 212 pregnant women recruited from two public hospitals in Italy were divided into two groups: (a) a pre‐COVID‐19 group composed of 141 expectant women (mean age = 34.6; SD = 4.3) at their third trimester before the national lockdown period; (b) a COVID‐19 group composed of 71 pregnant women (mean age = 33.3; SD = 4.5) at their third trimester during the COVID‐19 national lockdown. Participants completed two self‐report questionnaires: the Profile of Mood States and the Multidimensional Scale of Perceived Social Support. Moreover, the COVID‐19 group was asked to respond to an open question concerning worries about their pregnancies and COVID‐19. Results showed that pregnant women during COVID‐19 presented higher anxiety, depression and hostility, and lower vigour, than the pre‐COVID‐19 group. The main concerns were related to the effect of hospital restriction policies on childbirth and fears of contracting COVID‐19. Perceived partner social support represented a protective factor only for the pre‐COVID‐19 women. Limitations, strengths, and theoretical and clinical implications are discussed.